2021
DOI: 10.3389/fbioe.2021.790595
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Ankle Brace for Lower-Extremity Joints in Half-Squat Parachuting Landing With a Backpack

Abstract: Half-squat parachuting landing is a kind of activity with high impact force. Injuries on lower-extremity joints are common in half-squat parachuting landing and would be increased with a backpack. An ankle brace was used to prevent ankle injuries in landing. However, few quantitative studies reported about the protection of an ankle brace for lower-extremity joints in half-squat parachuting landing with a backpack. This study focused on evaluating the protective effects of an ankle brace in half-squat parachut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Niu et al suggested a linear relationship between peak vGRF and dropping height ( 33 ). Our previous study also demonstrated that wearing an ankle or knee brace reduced the peak vGRF, with the former showing enhanced effect ( 5 , 6 , 9 , 17 ). Our study suggested that wearing a brace reduced the peak vGRF by a maximum of 18.6%.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Niu et al suggested a linear relationship between peak vGRF and dropping height ( 33 ). Our previous study also demonstrated that wearing an ankle or knee brace reduced the peak vGRF, with the former showing enhanced effect ( 5 , 6 , 9 , 17 ). Our study suggested that wearing a brace reduced the peak vGRF by a maximum of 18.6%.…”
Section: Discussionmentioning
confidence: 63%
“…Since injuries associated with lower extremity joints (i.e., hip, knee, and ankle) and spine are more common during parachute landing, studies evaluating injury and its prevention are important for paratroopers ( 9 , 10 ). The ability to control the lower extremities upon landing is largely dependent on the motion of the lumbar spine ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…These volunteers (average: 71.3 ± 5.4 Kg and 25 ± 1.8 years old) had no acute lower extremity injury or previous ankle injury or surgery. Subjects with ankle braces, boots, and no braces were made to stand on the predefined platform and jumped down from different height platforms (152 cm, 82 cm, and 52 cm) on a force plate [6,10] (FP4060-08-100, Bertec, Inc., Columbus, Ohio, USA) (Figure 1). One foot landed on the board, and the other foot was on the force plate.…”
Section: Subjects and Experimental Measurementmentioning
confidence: 99%
“…Half-squat parachute landing in the Chinese Air Force is a kind of activity with high impact force [6]. The abnormal impact can change the kinematics and plantar loading of the lower extremities and increase injury risk [7].…”
Section: Introductionmentioning
confidence: 99%